SMALL - SCALE FISHERIES IN THE CONTEXT OF GLOBALISATION - John Kurien (cds, 1998)
The small-scale fisheries sector is the oldest and most important part of the marine fisheries economy of the world. Being a relative term, small-scale operations exist in most maritime nations. This is particularly true of the developing maritime countries where the small-scale sector normally accounts for the largest employment and a significant share of the fishery output. The future of the fisheries sectors in these countries will depend significantly on the manner in which their small-scale fisheries fare in the coming decades. One important factor determining this future is the nature and the impact which the recent new phase of globalisation of the world economy will have on this evolution. Taking a perspective from the developing Asian context, this paperfirst attempts to characterise the small-scale sector; provide an explanation for its continued resilience; examines some dimensions of the impact of the new globalisation on the sector; and provides a framework for suggesting some institutional arrangements and programmes of action to ensure its secure future